Linguistic Human Rights in Education - Szoszkiewicz, Łukasz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
Linguistic human rights are a concept remaining on the crossroads of several scientific disciplines, e.g. linguistics, anthropology, psychology and, last but not least, human rights law. Taking the latter as a lens, this study seeks to clarify the concept of linguistic human rights in education – presumably, the most linguistically sensitive sphere in the life of individuals and communities. The paper demonstrates that despite little mention of language in the UN treaties (ICESCR, CRC, CERD, CADE), its importance is reflected in the practice of the relevant treaty-based bodies. Moreover, increasing interest from scholars across a range of disciplines is contributing to the development of a linguistic human rights doctrine and is penetrating the UN human rights framework.